Analisis Majas Perbandingan Dalam Novel Sepasang Yang Melawan (2) Karya Jazuli Imam - Rianti Rianti; Septiana Pradyta (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to describe the figurative language used in the novel “A Pair Against (2)” by Jazuli Imam and to find out the author's style of writing. The type of research used is descriptive qualitative, the target of this research is to describe the comparative figure of speech in the novel